The Effect of Profit Persistence, Book Tax Differences and Capital Structure on Profit Quality with Accounting Conservatism as a Moderation Variable (Empirical Study on Service Companies Listed on the IDX for the 2021-2023 Period)" - Rudy Rahwana; Rida Prihatni; Ayatulloh Michael Musyaffi (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study aims to analyze the effect of profit persistence, book-tax differences, and capital structure on profit quality, with accounting conservatism serving as a moderating variable. Utilizing secondary data from the financial statements of service companies listed on the Indonesia Stock Exchange during the 2021-2023 period, the research employs a quantitative method with a causal design. The findings indicate that profit persistence has a positive effect on profit quality, suggesting that stable earnings are perceived as high-quality profits. Conversely, book-tax differences do not significantly impact profit quality, indicating that legal policy differences rather than manipulation may explain this relationship. Additionally, capital structure is shown to have a negative effect on profit quality, as higher debt levels may raise financial risk and lower market reactions to profits. Importantly, accounting conservatism is found to moderate the relationship between profit persistence and profit quality, as well as between book-tax differences and profit quality. Furthermore, it enhances the relationship between capital structure and profit quality, indicating that conservative accounting practices can improve the reliability of reported profits. This research provides valuable insights for investors and corporate management, highlighting the importance of profit quality and the need for effective management strategies to enhance financial reporting.